OPPORTUNITIES TO INCREASE THE STANDARD OF LIVING AND EMPLOYMENT OF THE POPULATION THROUGH THE DEVELOPMENT OF ECONOMIC ZONES (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article examines the opportunities to improve people's living standards and employment through the development of economic zones. Recommendations for the use of the algorithm for determining the required number of jobs in free economic zones have been put forward.